Intercity Railfares After HSR Liberalisation in Spain: Price Patterns in the Madrid–Barcelona Corridor - Santiago García-Samaniego; Javier Campos (Future Transportation, 2025)
This paper analyses the evolution of the prices of intercity high-speed rail (HSR) services operated by the Spanish public company, Renfe, on the Madrid–Barcelona route between April 2019 and June 2022. This period marks one of the most important events in the recent history of railways in Spain: the end of Renfe’s monopoly and the opening of this and other corridors to private competitors. Our main objective is to study the impact of the entry of the first competitor, Ouigo, on the incumbent’s pricing strategy. Our analysis confirmed that Renfe perfectly anticipated Ouigo’s entry and adjusted its prices about four months before the market opened. Interestingly, the incumbent also modified its tariff structure in advance according to the target customer’s willingness to pay. These results may be of interest for the forthcoming liberalisation of other intercity corridors.